The Influence of Socio Economics Characteristics and Meat Self-Sufficiency Policy on Beef Cattle Farmer’s Income in Indonesia - Wisnu Bawono; Sudi Nurtini; Ahmad Romadhoni Surya Putra (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
This study aimed to determine the influence of the implementation of the meat self-sufficiency policy on the cattle farmers’ income in Indonesia. This study used secondary data of Indonesian Family Life Survey (IFLS) that were collected in 2014. The IFLS are household data taken by survey at national level. This study used IFLS 5 data. The observed variables in this study included characteristics of farmer's household such as age, area of land cultivated, number of family members, education level, patterns integration of livestock farming and government assistance. Household income is derived from reduced revenue from agricultural sector and it cost as the dependent variable. The results of the study showed that mixed farming or livestock farming integration influenced farmer household income significantly (P<0.01). The cultivated land size affected the household income of farmers (P<0.01). The level of education, number of family members, type of assistance and age did not affect the income of household farmers. The Respondents were divided in two group, group that were exposed and those that were not to the meat self-sufficiency program. The results of study showed that government policy in meat self-sufficiency did not have a significant impact on the household income of farmers. The development of livestock in order to achieve self-sufficiency in meat needs to be